Answering the Call for Systems Change - Melanie Wilcox; Katharine Shaffer; Laura Reid Marks; Ashley Hutchison; Candice Hargons (Journal for Social Action in Counseling and Psychology)
There is much agreement within counseling psychology on the importance of social justice, yet social justice education and training remain limited in counseling psychology programs (Beerman et al., 2012; Pieterse et al., 2009; Singh et al., 2010). Critical components to social justice education and training include an emphasis on systems theories that could inform interventions (i.e. advocacy and activism) at the exosystem and mesosystem levels as well as learning about the breadth of activism and advocacy skills. Assessment, diagnosis, and conceptualization are considered core functional competencies in professional psychology (Fouad, 2009), yet these processes are often only taught at the individual level. If the goal of advocacy and activism are to foster systems change, considered a functional competency in counseling psychology (CCPTP, 2012), then it is crucial to provide systems-level theories and skills in counseling psychology education and training. We describe how we have attended to the provision of systems-level education and training in our respective programs. We will provide recommendations about the inclusion of systems-level theories, classroom formats, assignments, and mentorship designed to foster trainees’ development of a systems-level theoretical orientation, as well as skills to engage in social justice research, leadership, and both micro- and macro-level advocacy interventions.